1998
DOI: 10.1016/s0044-8486(98)00278-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen source and growth phase on proximate biochemical composition, lipid classes and fatty acid profile of the marine microalga Isochrysis galbana

Abstract: The marine microalga Isochrysis galbana was cultured in nitrate, nitrite or urea media to examine changes in the gross biochemical composition, with special emphasis on the growth phase associated changes in the compositions of the lipid classes and fatty acids. The gross biochemical composition was affected more by the growth phase than by the nitrogen source.Protein was higher during exponential growth (about 37-45% AFDW) but the pattern changed as the cultures aged, and lipids were the main algal constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
122
2
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(163 citation statements)
references
References 22 publications
24
122
2
9
Order By: Relevance
“…Aquat Microb Ecol 55: [219][220][221][222][223][224][225][226][227][228] 2009 duces a suite of polyunsaturated long-chain alkenes, alkenones and alkenoates (Volkman et al 1979, Marlowe et al 1984, Patterson et al 1994, Fidalgo et al 1998. Interest in the lipid composition of this species stems predominantly from the use of its long-chain (C 37 -C 40 ) alkenones as paleo sea surface temperature proxies (Prahl & Wakeham 1987).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Aquat Microb Ecol 55: [219][220][221][222][223][224][225][226][227][228] 2009 duces a suite of polyunsaturated long-chain alkenes, alkenones and alkenoates (Volkman et al 1979, Marlowe et al 1984, Patterson et al 1994, Fidalgo et al 1998. Interest in the lipid composition of this species stems predominantly from the use of its long-chain (C 37 -C 40 ) alkenones as paleo sea surface temperature proxies (Prahl & Wakeham 1987).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Moreover, other limiting treatments (5/1 and 0.5/1), being able to stimulate the synthesis of lipids [14,43,44], suffered a severe physiological restriction, which prevented them to express such stimulation. Then, there exists a nitrogen limitation threshold under which the strain would not be able to increase the concentration of lipids due to a metabolic block [45]. Contrary to what has been observed in other microalgae, D. salina Teodoresco is not capable of fixing gaseous nitrogen by means of an enzyme [46], therefore this nutrient shortage can only be mitigated by some external input of its environment.…”
Section: Effect Of Nitrogen Deficiency and Bubbling On The Content Ofmentioning
confidence: 99%
“…Many studies have shown that, the quantity and quality of lipids within the cell can vary as a result of changes in growth conditions such as temperature and light intensity, or nutrients, especially concentrations of nitrogen, phosphates and iron (Illman et al, 2000;Liu et al, 2008;Xin et al, 2010). Different nitrogen (N) sources and concentrations can affect the growth and biochemical composition of algae and change the amount of carotene and fatty acid (Fidalgo et al, 1998). While N limitation decreases, the cell density of the cultures, amount of biomass and amount of chlorophyll a, increase the organic carbon compounds such as the lipid in the biochemical structure of microalgae (Kilham et al, 1997;Pruvost et al, 2009).…”
Section: Introductionmentioning
confidence: 99%